Analisis Perbandingan Kinerja Keuangan Bank Konvesional dan Bank Syariah yang Terdaftar pada Indonesia: Studi Kasus Bank Syariah Mandiri dan Bank Mandiri - Nur fadhilah; Haryono; Rusliyawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to compare the financial performance between Bank Syariah Mandiri and Bank Mandiri in Indonesia in the period 2019-2023 using financial ratios. The financial ratios used consist of ROA, CAR, KAP, NPL, and LDR. The purpose of this study is to determine whether there is a difference between the financial report performance of Bank Syariah Mandiri when compared to Bank Mandiri. The analysis technique used to see the comparison of the financial performance of Bank Syariah Mandiri with Bank Mandiri is a quantitative method using SPSS. The results of the analysis show that there is a significant difference for each financial ratio between Bank Syariah Mandiri and Bank Mandiri. Bank Syariah Mandiri has better performance in terms of the LDR ratio, while Bank Mandiri has better performance in terms of ROA, CAR, KAP, and NPL